A preliminary study of the reproductive biology of Imbaw, Lucinoma annulata (Reeve, 1850). - Samentar, Lorena Palma (1997.)
Lucinoma annulata, a mud clam locally known as "imbaw" is an important fishery resource which supports the livelihood of some households in Guimaras. Thus, to properly manage this important and fast disappearing resource, knowledge of its reproductive biology is necessary. This study aimed 1) to histolgically describe the gonads of Lucinoma annulata and 2) to determine spawning peaks and reproductive cycle of the mud clam., Monthly samples were collected from July 1996 to February 1997. After the determination of the length and the GSI the clams were processed histologically. Histological examination showed that Lucinoma annulata may either be a hermaphrodite or a female . However, hermaphrodites were more frequently encountered in clams with shell length 25mm to 40mm and also in clams with shell lenght greater than 55mm. Females were predominant in individuals with shell lengths greater than 40mm to 55mm. Lucinoma annulata with size range from 25mm to 70mm in shell length were found to have either spermatozoa or vitellogenic oocytes in the gonad. However, in hermaphrodite specimens, the male system is the first to produce mature germ cells, which probably suggest a trend towards protandry. Data on GSI showed that the clam might be in active gametogenesis in October and November when GSI was high and spawned in December when GSI was relatively low. The presence of several small peaks implies that spawning is continous in this species. Moreover, the presence of juveniles in the mantle cavity of mature clams suggests brooding in this species. Hermaphroditism and brooding of the young observed in Lucinoma annulata may be an adaptation of this species to overcome difficulties in reproduction and survival.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Imbaw; Lucinoma annulata